Pengaruh Perceived Value Terhadap Minat Beli Virtual Goods: (Studi Pada Pemain Genshin Impact di Indonesia) - Rachma, Sophia Aulia; Sisilia, Kristina (eProceedings of Management, 2024)
Genshin Impact was one of the most searched games worldwide on Google in 2021. In its first year, it became the No.3 revenue-generating mobile game globally. The purpose of this study is to determine the effect of perceived value onpurchase intention of virtual goods on Genshin Impact players in Indonesia. The research method used is descriptiveanalysis research, using a quantitative approach. The total number of respondents obtained was 124 eligiblerespondents. The study used a non-probability sampling technique with purposive sampling method. The tests carriedout are classical assumption tests, simple linear regression analysis, and statistical tests. From the analysis ofperceived value (X), the average percentage is 80.20%, and the overall average percentage of purchase intentionvariables (Y) is 81.83%, which is in the good category. From the t test results, it can be seen that Perceived Value (X)has an influence on Purchase Interest (Y) Virtual Goods. It is known from the results of the coefficient ofdetermination analysis that the Adjusted R Square value of 0.438 is obtained, it can be concluded that the amount ofinfluence of the Perceived Value Variable (X) on Purchase Interest (Y) is 43.8%. While the remaining 56.2% isexplained by variables outside of the variables in this study.Keywords-perceived value, purchase intention, virtual goods, Genshin Impact.